Designing the user interface : strategies for effective human-computer interaction /: strategies for effective human-computer interaction. ([2018]) - Shneiderman, Ben; Plaisant, Catherine; Cohen, Maxine (Maxine S.); Jacobs, Steven M; Elmqvist, Niklas
No abstract available